2017
DOI: 10.1016/j.aos.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The moral mechanism of counter accounts: The case of industrial animal production

Abstract: Counter accounts are hoped to present a counterforce to hegemonic discourses and bring about emancipatory change in societies. While the political potential of counter accounts has, to an extent, been examined in prior accounting literature, there is a need to analyse the associated moral dimension. Our purpose in this paper is to advance theoretical understanding of the transformative potential of counter accounts by examining how they mediate the suffering of oppressed groups and how that mediation could lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 67 publications
(142 reference statements)
5
112
0
8
Order By: Relevance
“…Similar to the arguments of Belal et al, 2015;Brennan and Merkl-Davies, 2014;Gray et al, 2014b;Spence, 2009;Tregidga, 2017;Vinnari and Laine, 2017 and the iaNGOs felt that the inability of these marginalised communities to engage, the absence of their voice to speak their truth or to hold the powerful stakeholders accountable perpetuated the conflicts within the region. Resolving these conflicts required interventions from iaNGOs (and others) to create a significant shift in the power dynamics in favour of the indigenous communities.…”
Section: Addressing Power Inequalities Through Giving Voice and Greatmentioning
confidence: 97%
See 4 more Smart Citations
“…Similar to the arguments of Belal et al, 2015;Brennan and Merkl-Davies, 2014;Gray et al, 2014b;Spence, 2009;Tregidga, 2017;Vinnari and Laine, 2017 and the iaNGOs felt that the inability of these marginalised communities to engage, the absence of their voice to speak their truth or to hold the powerful stakeholders accountable perpetuated the conflicts within the region. Resolving these conflicts required interventions from iaNGOs (and others) to create a significant shift in the power dynamics in favour of the indigenous communities.…”
Section: Addressing Power Inequalities Through Giving Voice and Greatmentioning
confidence: 97%
“…Individual counter accounts can be combined with other external accounts that collectively problematise and present alternative solutions increasing the knowledge set that can inform arena engagements, dialogue, coalition building, and conflict resolution. Prior research on counter accounts and other forms of external accounts (Apostol, 2015;Dey and Gibbon, 2014;Gallhofer et al, 2006;Thomson et al, 2015;Tregidga, 2013Tregidga, , 2017Vinnari and Laine, 2017) has observed that these accounts play many different roles in conflicts. Evaluating external accounts in practice is therefore a complex process.…”
Section: Communities the Niger Delta Has Been Dramatically Changed Bmentioning
confidence: 99%
See 3 more Smart Citations